Hubungan Konsumsi Soft Drink dengan Kejadian Hipertensi di Sumatera Barat: Analisis SKI 2023 - Debby Ratno Kustanto; Immalatunil Khaira (STIKES Bina Usada Bali, 2026)
Background: The association between soft drink consumption and hypertension remains controversial, as many previous studies have not adequately controlled for potential confounding factors. Analyses incorporating complex survey designs are needed to provide more accurate estimates of this association. Objective: To examine the independent association between soft drink consumption and hypertension among adults in West Sumatra Province after adjusting for sociodemographic and health-related behavioral factors. Methods: This cross-sectional study analyzed data from the 2023 Indonesian Health Survey (SKI), including 24,910 respondents aged ≥15 years in West Sumatra Province. Data were analyzed using a complex survey approach that accounted for sampling weights, stratification, and primary sampling units (PSUs). Associations were assessed using the design-based chi-square test, followed by complex logistic regression to estimate adjusted odds ratios (aORs). Results: The prevalence of physician-diagnosed hypertension was 7.1%. Bivariate analysis initially showed a significant inverse association between soft drink consumption and hypertension (p<0.001). However, after adjustment for age, sex, smoking status, and physical activity, the association was no longer statistically significant (aOR=1.155; 95% CI: 0.884–1.510; p=0.290). The strongest determinants of hypertension were older age (p<0.001), smoking (aOR=1.424; p=0.002), and insufficient vigorous physical activity (aOR=1.326; p=0.001). Conclusion: Soft drink consumption was not independently associated with hypertension among adults in West Sumatra. The significant association observed in the bivariate analysis reflected confounding, primarily due to the predominance of younger individuals among soft drink consumers